On the application of Ateb-functions to the construction of a solution of a nonlinear Klein-Gordon equation - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For a nonlinear Klein-Gordon equation, we construct the first approximation of an asymptotic solution by using Ateb-functions. The resonance and nonresonance cases are considered.